Banking Securitization with Shares and its Relationship to the Purposes of Legitimate Investment - Mansour, Yasmeen Mohammad Khaled (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This research deals with an important topic of contemporary banking issues, which is bank securitization by shares, and it is represented in clarifying what is meant by bank securitization by shares, its image and its adaptation, and clarifying the ruling on bank securitization by shares through a statement of its relationship to the sample and organized banking securitization, then clarifying the relationship of bank securitization by shares to the legitimate purposes of investment legit. Methods: The research followed the deductive inductive approach in studying this topic, and showing the relationship of banking securitization with shares to the legitimate purposes of legitimate investment. Results: One of the most important findings of the research is that bank tawarruq with shares is adapted as a sale of the sample, as it is a legal ploy to legalize usury, and it takes the rule of prohibition. This is the forbidden trick that leads to usury, and it has also appeared that the purposes of legitimate investment are represented by several important purposes, and all of these purposes in investment are reflected in banking transactions, so the legal aspect and the controls that must be paid attention to when practicing any financial and banking transaction must be taken into account. Conclusion: Banking tawarruq with shares in its entirety is based on the Sharia trick, and the aim of the Sharia is to achieve its purposes of investing money in a legal way that keeps all transactions away from any Sharia violation.